2020
DOI: 10.1371/journal.pone.0243096
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery programmes versus conventional care in bariatric surgery: A systematic literature review and meta-analysis

Abstract: Background With obesity prevalence projected to increase, the demand for bariatric surgery will consequently rise. Enhanced recovery programmes aim for improved recovery, earlier discharge, and more efficient use of resources following surgery. This systematic literature review aimed to evaluate the evidence available on the effects of enhanced recovery programmes after three common bariatric procedures: laparoscopic Roux-en-Y gastric bypass (LRYGB), laparoscopic sleeve gastrectomy (LSG), and one anastomosis g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
1
1
Order By: Relevance
“…Moreover, PONV is the leading cause of delayed discharge and readmission after bariatric surgery 50 , 51 . The 30-day readmission rate was significantly lower in the ERAS group, which differs from that observed in previous studies 41 , 44 , 45 . This may be due to the larger sample size.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, PONV is the leading cause of delayed discharge and readmission after bariatric surgery 50 , 51 . The 30-day readmission rate was significantly lower in the ERAS group, which differs from that observed in previous studies 41 , 44 , 45 . This may be due to the larger sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the ERAS protocol was implemented relatively late in bariatric surgery. Several meta-analyses have concluded that the ERAS protocol significantly decreases the length of hospitalization in patients undergoing bariatric surgery 41 , 44 , 45 . Nonetheless, these studies failed to clarify the importance of ERAS in minimally invasive bariatric surgery, even though this surgical approach is strongly recommended 14 .…”
Section: Discussionmentioning
confidence: 99%